UPAYA PENINGKATAN RESILIENSI PADA IBU HAMIL DI GEREJA HATI YESUS YANG MAHA KUDUS NOEMUTI KABUPATEN TIMOR TENGAH UTARA - Yosefa Sarlince Atok; Maria Vilastry Nuhan; Muhammad Saleh Nuwa; Roslin Evelin Sormin (Universitas Mataram, 2022)
Pregnancy is generally considered a happy moment, especially for the mother. But the overflow of feelings feels different when pregnancy occurs during the COVID-19 pandemic. For some women, pregnancy makes them more vulnerable to mental problems or psychological disorders because of the inability to adjust to the various changes that occur during pregnancy. The purpose of this activity is to increase the resilience of pregnant women during the Covid-19 pandemic. This empowerment and education activity can provide benefits to pregnant women so that they have mental capabilities and perform coping mechanisms during pregnancy. The method used is health education. The activity was carried out in 3 stages, namely the preparation of facilities and infrastructure, the socialization and evaluation stages. The targets and partners in this activity are pregnant women, lecturers and students of the Midwifery Study Program at STIKes Maranatha Kupang. The result of this activity is that this counseling was attended by approximately 45 pregnant women. The participants seemed enthusiastic about the material presented by the resource persons and were able to be actively involved so that this outreach activity took place in a two-way system. In accordance with the results of the evaluation that was carried out orally before being given counseling, it was found that 55% of pregnant women felt anxious and did not know for sure how to prepare for pregnancy and childbirth, while based on the results of the final evaluation after being given counseling, 80% of pregnant women were more prepared to face pregnancy and become resilient. if problems occur during pregnancy. The conclusion of the implementation of resilience counseling is that pregnant women are more prepared and improve coping and resilience mechanisms and create Subjective Well-Being in pregnant women.